Burundi’s ‘worst enemy’: The country’s fight against COVID-19 - Manirambona, Emery; Reddy, Henna; Uwiringiyimana, Emmanuel; Uwizeyimana, Theogene; Kamath, Archith; Parepalli, Sai Arathi; Ruzats, Salvador Sun; Ntacyabukura, Blaise; Islam, Sheikh M. S.; Ahmadi, Attaullah; Lucero-Prisno III, Don E (Kesmas, 2021)
Coronavirus disease 2019 (COVID-19) has proved to be a severe global public health threat, causing high infection rates and mortality worldwide. Burundiwas not spared the adverse health outcomes of COVID-19. Although Burundi’s initial response to the COVID-19 pandemic was criticized, hope arose in June2020 when the new government instituted a plan to slow virus transmission that included public health campaigns, international travel restrictions, and masstesting, all of which proved effective. Burundi has faced many challenges in containing the virus, the first of which was the lack of initial preparedness and appropriate response to COVID-19. This was exacerbated by factors including shortages of personal protective equipment (PPE), limited numbers of life-savingventilators (around 12 ventilators as of April 2020), and the presence of only one COVID-19 testing center with less than ten technicians in July 2020.Moreover, as Burundi is amongst the poorest countries in the world, some citizens were unable to access necessities such as water and soap, required forcompliance with government recommendations regarding hygiene. Interestingly, Burundi did not implement a nationwide lockdown, allowing mass gatheringsand public services to continue as usual due to a firm belief in God’s protection. As the daily confirmed cases have tripled since December 2020, Burundi mustprepare itself for the threat of a new wave. Establishing precautionary measures to contain the virus and strengthening the health surveillance system inBurundi would significantly positively impact the prevention and management of COVID-19.